ADVANCE CARE PLANNING IN JAPANESE HOSPITALS-USEFULNESS OF END-OF-LIFE CARE TEAM. Issue 2 (1st June 2013) - Yokoe, Y; Nishikawa, M; Kubokawa, N; Fukuda, K; Hattori, H; Yong-Jae, H; Miura, H; Endo, H; Nakashima, K
Abstract : Background: Although advance care planning (ACP) in hospitals is important, the best means of promoting it in Japan remain to be clarified. Aim: The primary aim of this study was to evaluate the usefulness of end-of-life care teams (EOLCTs) for both cancer and non-cancer patients. The secondary aim was to evaluate the usefulness of narrative life reviews and ACP conducted by full-time EOLCT nurses using qualitative analysis. Methods: We conducted the 'three-pillar strategy for decision making' for the families of 209 patients. There are three large pillars, (1) patient's wishes; (2) family's wishes; and (3) medical judgment. There are also three key pillars in regard to patients' wishes: (1) 'Present': Regardless of the patient's competence/incompetence, any subtle signs shown by the patient must be noted; (2) 'Past': ACP and narrative life reviews must be checked; and (3) 'Future': The best future interests must be considered. The patient's wish is the most important pillar. Results: Intervention by the three-pillar strategy in EOLCT decision making tended to increase the number of home deaths in accordance with patients' wishes in collaboration with the home care support ward. Narrative life reviews by nurses led to enhancement of ACP. Discussion: The most important finding was that patients' and their families' wishes were respected. Conclusion: The three-pillar strategy used by EOLCT in decision making was useful in enhancing hospitals' ACP.